Campaigns, Movements, and Games for the Development of Reading Culture - Gombos, Péter; Hevérné Kanyó, Andrea (Acta Scientiarum Socialium, 2015)
Campaigns, Movements, and Games for the Development of Reading Culture Nowadays we can often hear that the young ones of today do not read (enough), they do not read the right texts, they do not read them in the right way and if they read something at all, they do not understand them properly (or at all). In our study we would like to present part of the initiatives which could be effective concerning the education of readers, the ’accustoming’ of the younger and the older ones to reading. We mention native and foreign examples as well which have worked on the internet, which have been found out like quiz shows, but there are facebook campaigns and lightning throngs among the chosen ’good practices’, too. Naturally, the examples from Kaposvár have been stressed a lot, from among several practices have fortunately become well-known throughout the country.
Keywords: Campaigns; movements; games for the development of reading culture